A review of studies on virtual layout and atmospherics - potential applications to the fashion industry. Issue 4 (8th August 2021) - Roberts, Jenniefer; Grassi, Alessia
ABSTRACT: Retail layouts and atmospherics have been widely investigated within the physical retail environment, Research suggests that there is limited understanding of these elements in the virtual environment despite the fact that they would appear to be the easiest and most effective combination to implement by online fashion retailers. Considering potential applications in the fashion industry, a review of current literature on layout and atmospherics has identified the freeform layout as a valuable format for online fashion retailing. The freeform layout has been found to increase consumers' hedonic motivations to purchase. Furthermore, design and visual cues have a significant influence on consumers, while aural cues despite being very important to the consumers' experience appear to be underexploited in the online fashion space. This paper contributes a review of established retail elements, and identifies those that adapt well from the offline to online retail environment.